Gestión y creación de nuevos contenidos audiovisuales de Bang Estudio. - Peñafiel Villavicencio, Johanna Lissette (2016)
In this article the issue of management and creation of new digital media content as a tool that will determine the quality and validity, availability and display of every audiovisual documents presented. The theme of the audiovisual image is also treated as a strategy for research by observation and joining the means of production and postproduction of audiovisual content thus enabling a deep operation of this tool approach also is made of concrete a collection of information as an active part of this investigation. Projecting generally a brief history of the beginnings or were created these media, construction , management and distribution by large transnational technology companies, and some reflections on the use of digital imaging the importance genre cybernetics the network usage , web management and creation of new audiovisual content.